Effects of network relations on destination development and business results. (February 2022) - Elvekrok, Ingunn; Veflen, Nina; Scholderer, Joachim; Sørensen, Bjarne Taulo
Abstract: Taking a firm perspective, this study investigates cooperation in a destination network in a mountain village in Norway. 51 organizations participated in a survey, indicating their main cooperation partners and assessing the value of each cooperation in terms of ten intermediary benefits (increased sales, reduced costs, etc.) and two ultimate outcomes (business results, destination development). Firms perceived a cooperation to contribute to business results if the cooperation had led to increased sales or made the firm more resilient to market fluctuations. Firms perceived a cooperation to contribute to destination development if the cooperation had led to new knowledge, improved customer satisfaction, and hat not simply helped improve operations. The findings demonstrate the interconnectedness of intermediate and ultimate relationship outcomes on firm and destination level. The study contributes to a more comprehensive understanding of network relations, relevant to the literature on relational benefits and destination development.